Pruning Shoots and Aplication of Inorganic Fertilizer in Chili Plant (Capsicum annuum L.) - Anthony Walsen; Marthini K. Lesilolo; Fransin Polnaya (Faculty of Agriculture, Pattimura University, 2023)
Pruning and fertilizing chili plants can increase fruit production per plant. This study aims to determine the impact of pruning and application of inorganik fertilizer on the growth and production of chili (Capsicum annuum L.) This study used a randomized block design (RBD) method using 2 factors and 3 repplication. The first factor was the pruning treatment (C) which consisted of 2 treatments: C0=without pruning and C1=with pruning. Factor II was the treatment of inorganic fertilizer were : TSP (P) fertilizer added to NPK compound fertilizer with 5 levels of concentration, namely: P0=0 g TSP + 0.5 Kg NPK/5 liters of water, P1=200 g TSP + 0.5 Kg NPK/5 liters of water , P2=400 g TSP + 0.5 Kg NPK/5 liters of water, P3=600 g TSP + 0.5 Kg NPK/5 liters of water, and P4=800 g TSP + 0.5 Kg NPK/5 liters of water. The results showed that the interaction between pruning and the application of TSP fertilizer added to the NPK compound fertilizer had a significant effect on the growth and production of large chili plants. The pruning treatment has a very significant effect on the growth and production of chili plants, especially on the number of branches, the number of flowers, and the number of fruits formed. Provision of TSP fertilizer added to NPK compound fertilizer with concentrations of P = 0.25% and P = 0.29% were able to have a significant effect on the formation of branches and flowers of chili plants.